Evaluation of Practical Diets Containing High Levels of Corn Distillers Dried Grains with Soluble on Red Tilapia Floating Net Cage Production Performance - Suprayudi, Muhamad Agus; Yaniharto, Dedy; Priyoutomo, Nurbambang; Kurnianto, Ari; Ekasari, Julie; Jusadi, Dedi; Haga, Yutaka (Pakistan Journal of Nutrition, 2015)
A feeding trial was performed in floating net cages located in Cirata Reservoir, West Java, Indonesia to evaluate the use of high levels of distillers dried grains with soluble as in practical diets of red tilapia. Red tilapia Oreochromis sp. with an initial average body weight of 31.59±1.07 g was randomly distributed into 12 units of floating net cage (2 x 2 x 1.5 m) at a density of 25 fish/m2 and fed to satiation 3 times daily for 120 days of culture period. Isonitrogenous and isocaloric experimental diets with 3 different levels of DDGS inclusion, i.e., 20, 30 and 40% were prepared at average protein and energy levels of 28% and 424 kcal/100 g of feed, respectively. A commercial feed with a protein level of 30% and energy level of 408 kcal/100 g of feed was used as a control diet. Fish survival in treatments C with 40% DDGS inclusion level (93.67%) was significantly higher (p<0.05) than other treatments except treatment D (88.90%). There was no significant difference observed in fish final weight, weight gain, as well as specific growth rate in between treatments, however feed efficiency and protein retention of DDGS treatments were significantly higher than the control. This study demonstrates that diets without fishmeal with DDGS inclusion levels up to 40% provides good growth performance and is economically viable for red tilapia cage production.